Effects of dapagliflozin on inflammatory and apoptotic markers in rats exposed to cyclophosphamide-induced hepatotoxicity: comparison with silymarin - Hlail, Afrah Thiab; Al-Shawi, Nada Naji (Pharmakeftiki, 2025)
Cyclophosphamide (CPA) is a widely used chemotherapeutic agent; however, its clinical utility is constrained by dose-dependent hepatotoxicity. This study evaluated the hepatoprotective effects of dapagliflozin (DAPA), a sodium-glucose co-transporter 2 (SGLT2) inhibitor with known anti-inflammatory properties, in comparison to silymarin (SILY); a well-established hepatoprotective flavonoid. Fifty Wistar rats were randomly assigned to five groups: (i) negative control, (ii) vehicle control receiving 2% sodium carboxymethyl cellulose, (iii) CPA-treated (30 mg/kg/day), (iv) CPA + DAPA (3 mg/kg/day), and (v) CPA + SILY (200 mg/kg/day). All treatments were administered for ten consecutive days. CPA administration significantly elevated hepatic levels of tumor necrosis factor alpha (TNF-α; a pro-inflammatory cytokine), while reducing interleukin-10 (IL-10; an anti-inflammatory mediator), thereby aggravating liver injury. DAPA was more effective than SILY in attenuating inflammation and restoring IL-10 levels. Furthermore, CPA markedly increased expression of caspase-3 (a pro-apoptotic marker) and decreased B-cell lymphoma 2 (BCL-2; an anti-apoptotic protein), indicating enhanced apoptotic activity. Both DAPA and SILY ameliorated these apoptotic changes, with DAPA exerting a more pronounced anti-apoptotic effect. In conclusion, DAPA demonstrated superior hepatoprotective efficacy compared to SILY, characterized by stronger anti-inflammatory and anti-apoptotic actions. These findings support the potential of DAPA as a therapeutic candidate for CPA-induced hepatotoxicity, warranting further investigation into its clinical applicability and possible synergistic use in combination therapies.